THE LEGALITY OF THE BOARD OF DIRECTORS OF STATE-OWNED ENTERPRISES' CURRENT POSITIONS REGARDING PRICE FIXING AGREEMENT VIOLATIONS - Puteri Nurjanah; Elisatris Gultom; Anita Afriana (Universitas Lampung, 2022)
The relationship between concurrent positions and price-fixing is explained in the Business Competition Supervisory Commission (